COVID-19: Unveiling the Neuropsychiatric Maze -- From Acute to Long-Term Manifestations (2024)
The SARS-CoV-2 virus has spread rapidly despite implementing strategies to reduce its transmission. The disease caused by this virus has been associated with a diverse range of symptoms, including common neurological manifestations such as dysgeusia, anosmia, and myalgias. Additionally, numerous cases of severe neurological complications associated with this disease have been reported, including encephalitis, stroke, seizures, and Guillain–Barré syndrome, among others. Given the high prevalence of neurological manifestations in this disease, the objective of this review is to analyze the mechanisms by which this virus can affect the nervous system, from its direct invasion to aberrant activation of the immune system and other mechanisms involved in the symptoms, including neuropsychiatric manifestations, to gain a better understanding of the disease and thus facilitate the search for effective therapeutic strategies.